Odpowiedź:
a)
(2b - 7) - (-12 + 5b) = 2b - 7 + 12 - 5b = -3b + 5
b)
8n - 3k + (-8k + 12n) = 8n - 3k - 8k + 12n = 20n - 11k
c)
-(b + 9) - (-9 + 7b) = -b - 9 + 9 - 7b = -8b
d)
-6x - (3 + 5x) - 3 = -6x - 3 - 5x - 3 = -11x - 6
e)
8 - 3y - (-7 - y + 5) = 8 - 3y + 7 + y - 5 = -2y + 10
f)
3 + (8u - 5) - (5u + 2) = 3 + 8u - 5 - 5u - 2 = 3u - 4
g)
7z - (3 - 4z) - (5 - z) = 7z - 3 + 4z - 5 + z = 12z - 8
h)
w - 5w² - (w² + 3w) - (4w - 6w²) = w - 5w² - w² - 3w - 4w + 6w² = -6w
i)
-(5xy + 5yz) - 12yz + (-3xy + yz) = -5xy - 5yz - 12yz - 3xy + yz = -8xy - 16yz
j)
8p - (3 - 4p - r) - (2 + 3p + 5r) = 8p - 3 + 4p + r - 2 - 3p - 5r = 9p - 4r - 5
Szczegółowe wyjaśnienie: